On Crossing Boundaries - Juruś, Dariusz (Roczniki Nauk Społecznych, 2025)
The article outlines the issue of crossing boundaries in art, starting with Marcel Duchamp, through conceptualism, and ending with bioart and zoesthetics. The focus was on the conceptual side of this phenomenon, while omitting its social, political and cultural dimensions. It is indicated that this crossing of boundaries evolved from the conceptual to the physical dimension. In this context the post-humanist approach – in which this crossing of boundaries places man not in a vertical, but a horizontal dimension, reducing him to the world of plants and animals – was critically assessed. It was also pointed out that from this perspective, the contemporary trends characterized here refer directly to the Darwinian vision of life, in which the boundaries at the level of micro and macroevolution are abolished.